Republic of Poland : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2013)
This paper on the Republic of Poland's Financial System Stability Assessment highlights economic policies and development. Skillful policy management and sound fundamentals have allowed the economy to weather the global financial crisis, and the euro area turmoil. Risk drivers include slow growth abroad and domestically, rising unemployment, and declining residential real estate prices. Vulnerabilities lie in interconnectedness with the euro area, and exposure to foreign exchange risk and foreign investors, which in turn may pressure bank funding, especially in the absence of long-term domestic funding sources. Stress tests suggest that vulnerabilities are not likely to become systemic, though some pockets of weakness were identified.